Distribuiç\~ao desigual dos direitos humanos e da cidadania: Áreas de concentraç\~ao de vítimas de homicídio e aç\~ao policial no município do Rio de Janeiro - Patricia Silveira Rivero (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– In Brazil, homicide rates are beginning to be high in terms of international comparison since the 80`s until today Rio de Janeiro appears as one of the cities where this phenomenon draws more attention. This article is an attempt to identify some of the causes of the high number of violent deaths in this city through the analysis of geo-referenced database of victims of homicide between 2002 and 2006. This result proves the existence of patterns of distribution of deaths within that reveal the deepening of social segregation of slum`s populations and of the most populous and poorest neighborhoods, the most affected by the concentration of victims. It is also confirmed the concentration of the number of civilians killed by police in these areas, making the areas of poverty in places where citizenship is scarce and do not comply with fundamental human rights and respect for life and safety.
Keywords: K42; R58; 330